ANALISIS TANGGUNG JAWAB BANK TERHADAP NASABAH PADA PRODUK INVESTASI REKSADANA - Herman, Emillia; Lesatari, Rika; Hendra, Rahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Besides banks as intermediaries in capital markets, is used as a place to deposit funds of its customers, the storage function is referred to as the custodian bank. In fact some of the Bank transferred all responsibility to the customer. Based on this, the authors are interested in doing legal research shaped thesis with the title